2003
DOI: 10.1183/09031936.03.00048103
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and anti-inflammatory responses in respiratory syncytial virus bronchiolitis

Abstract: Respiratory syncytial virus (RSV) bronchiolitis is an important cause of severe respiratory disease in infants. This study aimed to characterise changes in pulmonary pro-and anti-inflammatory responses in infants with RSV bronchiolitis over the course of the illness.On the day of intubation (Day 1) and the day of extubation (Day X), nonbronchoscopic bronchoalveolar lavage was performed on term and preterm infants ventilated for RSV bronchiolitis and on control infants on Day 1. Tumour necrosis factor (TNF)-a, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 30 publications
7
77
1
9
Order By: Relevance
“…This observation suggest that a mixed T H 1/T H 2 response is generated at the first stage of the disease. 79 Consistently with this observation, a mixed T H 1/T H 2 response was also observed in the lung of hRSV-infected mice, although with a significant increase of IL-13, which is known to induce airway hyperreactivity. 80,81 The predominant T H 2 immune response observed in infants and children could be due to the capacity of hRSV to polarize the adaptive immune response from a protective T H 1 phenotype to a T H 2-type response.…”
Section: An Adequate Cd4supporting
confidence: 70%
“…This observation suggest that a mixed T H 1/T H 2 response is generated at the first stage of the disease. 79 Consistently with this observation, a mixed T H 1/T H 2 response was also observed in the lung of hRSV-infected mice, although with a significant increase of IL-13, which is known to induce airway hyperreactivity. 80,81 The predominant T H 2 immune response observed in infants and children could be due to the capacity of hRSV to polarize the adaptive immune response from a protective T H 1 phenotype to a T H 2-type response.…”
Section: An Adequate Cd4supporting
confidence: 70%
“…TNF-a is known as a potent mediator of inflammation and plays a key role during the inflammatory responses of hRSV bronchiolitis (Becnel et al, 2005;McNamara et al, 2004;Morrison et al, 2007). TNF-a may play a protective role in RSV infection (Neuzil et al, 1996).…”
Section: A F G Antonis and Othersmentioning
confidence: 99%
“…IL-17-producing T cells are induced in primary infections through pathways that involve STAT3 and IL-6 (16,17). High levels of IL-6 have been found in the airways of infants with RSV bronchiolitis (18,19), and a number of studies have identified IL-17 in the airways (20)(21)(22)(23)(24) and plasma (21,24) of infants with RSV infection. Two studies have found lower levels of IL-17 in the airways of the most severely affected infants, and the authors suggested that higher IL-17 levels were associated with protection against more severe disease (21,24).…”
mentioning
confidence: 99%